Self-reported oral health and oral health-related quality of life among older adults receiving home care services in South-eastern Norway - Hero Ibrahim Hassan; Marte-Mari Uhlen-Strand; Vibeke Ansteinsson; Ragnhild Hellesø; Ewa A. Sz. Hovden; Rasa Skudutyte-Rysstad (Acta Odontologica Scandinavica)
Objective: To map self-reported oral health status, oral health-related quality of life (OHRQoL), and associated factors among older adults receiving home care services (HCS) in south-eastern Norway.